2021
DOI: 10.3390/ijerph18179390
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Model for Community Based Oral Cancer Screening Program: Outcome from 4 Northeastern Provinces in Thailand

Abstract: Management of advanced-stage oral cancer adds a great burden to individuals and health care systems. Community-based oral cancer screening can be beneficial in early detection and treatment. In this study, a novel oral cancer screening program was conducted utilizing an existing network of health care personnel, facilities, and digital database management for efficient coverage of a large population. The screening program considered 392,396 individuals aged ≥40 from four northeastern provinces in Thailand. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Of the 16 studies (Table 1), 15 were conducted in Asia, including 4 each in Taiwan, India, and China and 1 each in Singapore, Japan, and Thailand . The only study performed outside Asia was from Portugal.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 16 studies (Table 1), 15 were conducted in Asia, including 4 each in Taiwan, India, and China and 1 each in Singapore, Japan, and Thailand . The only study performed outside Asia was from Portugal.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were community-based clustered randomized clinical trials (RCTs), including 3 studies reporting data from a 15-year RCT in Kerela, India, and 2 studies showing the preliminary and interim results from a 5-year RCT in southern China. The remainder were observational studies, including 5 cohort studies, 3 case series, and 3 cross-sectional studies . A control group was assessed in 10 studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that screening with COE in individuals with highrisk behaviour (tobacco and/or alcohol users) leads to a significant reduction in oral cancer incidence and mortality in the long run (Sankaranarayanan et al, 2005). In the community based oral cancer screening program conducted in Thailand, 88,201 individuals were screened by dental auxiliaries and 544 oral potentially malignant disorders (OPMDs) and 1,047 non-OPMDs were identified by the dentists (Klongnoi et al, 2021). A district-level oral cancer screening program conducted at 48 panchayats of Kannur district in Kerala, India, proved that trained FHW could be effectively used in oral cancer screening programs agreeing with our review (Philip et al, 2018).…”
Section: Clinical Applicabilitymentioning
confidence: 99%